Reflexões sobre uma filosofia da tecnologia no pensamento de John Dewey - Tavares, Rossano Soares (2007)
The purpose of this dissertation is to analyze on the set of production of John Dewey the philosophical reflection about technology and create a relationship with pragmatic theory. John Dewey, American philosopher, pragmatic, wrote about several subjects, between them, democracy, politics, liberty, knowledge and education. Dewey didn´t write directly about technology in his books and articles, but that subject always was considered. To make the development of that analyze the main books of John Dewey were studied and the books of professor Larry Hickman were too, professor Hickman is one the main commentator of Dewey´s production. The methodology used include too the read of several articles of newspapers and magazines, especially that from Society for Philosophy and Technology and Society of Technology. Technology came from technique (that affirmation will be detailed) and the application of technique by man date back for distant past and thus is salutary and necessary that this dissertation came back ancient Greece to search the techniques available in that epoch and supports the technology exist today. The technology nowadays has an important role in our society establish a multidiscipline relation with several areas. Only to give a example, technology is present on Mathematics, Medicine, Geography, Communication, Semiotics, Engineer and Science. Its sounds stranger, but the science got big advances because the development of technology. Without doubts, we can affirm that the modern society established a very high degree of dependence in relation the use and application of technology. Therefore, technology deserves to be object of reflection and critics by philosophers too, because the impacts generate to the society are enormous and them are directly related with theories and subjects largely studied by philosophy, for example: Esthetics, Ethics, Techniques, Power, Politics, Democracy and Knowledge. Technology reflects too and generates discussions in areas that are not object of studies of philosophy, for example: Economics. In such case, a philosophical discussion is necessary to support society in the inquiring by the truth and too in the solution of the problems presented by use and development of technology. If philosophy doesn´t treat the subject technology, we will be exposed to the risk of others disciplines make this, generating absolutes truths distant of society s needs. Have the technologist and technician knowledge to answers the demands of society? Is it possible society earn by the use of technology avoiding in secure way the risks inserted in this use? In that analyse is possible identify what Dewey was always concerned with these questions, and between others, focusing the positives aspects of using technology without disdain of risks involved